2002
DOI: 10.1038/sj.leu.2402541
|View full text |Cite
|
Sign up to set email alerts
|

BCRP gene expression is associated with a poor response to remission induction therapy in childhood acute myeloid leukemia

Abstract: Breast cancer resistance protein (BCRP), also known as mitoxantrone resistance protein (MRX) or placenta ABC protein (ABC-P), is the second member of the ABCG subfamily of ABC transport proteins (gene symbol ABCG2). Transfection and enforced expression of BCRP in drug-sensitive cells confers resistance to mitoxantrone, doxorubicin, daunorubicin and topotecan. In this study the expression of BCRP gene was measured using TaqMan real-time PCR in 59 children with newly diagnosed AML. Nine patients were also analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(127 citation statements)
references
References 14 publications
6
120
1
Order By: Relevance
“…21 Alternatively, mechanisms other than MDR1 might be responsible for the development of clinical drug resistance. [22][23][24] Cure rate in AML has improved with intensive induction and postremission therapy with optimized timing. The best results were obtained with the most drug-intensive regimens.…”
Section: Maintenance Therapymentioning
confidence: 99%
“…21 Alternatively, mechanisms other than MDR1 might be responsible for the development of clinical drug resistance. [22][23][24] Cure rate in AML has improved with intensive induction and postremission therapy with optimized timing. The best results were obtained with the most drug-intensive regimens.…”
Section: Maintenance Therapymentioning
confidence: 99%
“…In fact, some reports have shown an association between BCRP expression and a poor response to chemotherapy. For example, the expression of BCRP has been reported in leukemic cells (13) and solid tumors (14-16) from patients, and increased expression of BCRP has been implicated in resistance to induction therapy against childhood acute myeloid leukemia (17). Furthermore, it has been reported that levels of BCRP are higher in cases of hepatic metastasis after irinotecan-based chemotherapy than in cases of irinotecan-naive metastasis (18), and BCRP impacts clinical outcome in platinum-based chemotherapy for advanced non-small cell lung cancer (19).…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the significance of BCRP in AML is unclear, possibly reflecting the use of different assays in different studies. [6][7][8][9][10][11][12][13] Little is known about the correlation between BCRP assays in AML. We studied expression of wild-type and mutant BCRP mRNA, expression of BCRP protein detected by the three available BCRP-specific monoclonal antibodies and function of BCRP in eight cell lines with different levels of BCRP-mediated resistance and in blasts from 31 untreated AML patients.…”
Section: Introductionmentioning
confidence: 99%